Potential Benefit of Flavonoid in Papaya Leave Gel in Neutrophil, Angiogenesis, and Wound size in Rattus Norvegicus - Siti Nurhidayah; Iin Tri Marlinawati; Sri Winarsih; Tatit Nurseta (Medical Laboratory Technology Journal, 2022)
An incision wound is the destruction of several cells in the skin area that has experienced an incision. Several factors influencing wound healing are neutrophils as causative agents of inflammation, angiogenesis, and wound closure. These three factors should undergo physiologically to obtain the optimal healing process. Currently, herbal products are preferred because they have lower side effects than synthetic ones. Papaya leaves contain flavonoids with various functions, including wound closure and anti-inflammatory and antioxidant effects. Topical intervention, especially gel, is good for healing because it can keep the wound moist. This research aimed to determine the effect of the administration of papaya leaf gel on wound closure, neutrophil, and angiogenesis. Thirty white rats were used as the model animals in a randomized experimental study divided into five groups comprising negative control (0,9% NaCl), positive control (10% Povidone-iodine), and three intervention groups treated with gel of Carica papaya leaves at a dosage 10%, 20%, and 30%. All groups were topically administered treatment once a day on the dorsal surface for seven days. Carica papaya leaves contain flavonoids, saponin, tannin, and alkaloids qualitatively and 7,734 mg/kg of the flavonoid quantitatively. There were no significant differences in wound size in all three groups on three days, but Carica papaya leave gel had a superior effect compared to 10% PI and 0,9% NaCl in the wound closure process. There were significant differences in all groups in neutrophil and angiogenesis. Nevertheless, 20% papaya leave gel showed the lowest number of neutrophils and had a superior effect on improving the new blood vessels significantly compared to negative and positive groups.